Foray in a Modern Reserve: An Impounding Portrait of Land Use - Wilson, Robin (Writingplace, 2020)
During research for the Arts Council funded project East Sussex Modern (2016), Photolanguage (Nigel Green & Robin Wilson), visited sites relating to the legacy of the modernist Borough and Water Engineer Sidney Little (1885-1961) in the county of East Sussex, U.K.. These included the impounding reservoirs of Powdermill (1932) and Darwell (1949). The landscapes surrounding the reservoirs have evolved into mature woodland nature reserves and represent complex terrains of land-use and property ownership. ‘Foray in a Modern Reserve’ (Part I), an image and text ‘portrait’ and re-imagining of these terrains, is a composite text, an assemblage of diverse texts of occupiers and users of these terrains over time, from Photolanguage’s own observations made on site visits, to the archival records of Sidney Little’s description of the reservoir infrastructure, to the accounts of UCL archaeologists, Angling and Ramblers clubs and local landowners. It is a vehicle through which to explore an experimental method of spatial writing at the intersection of archival research, visual and textual documentary practice, and visual and textual fiction-practice. Imagery interplays with the text’s narrative structure to generate its own narrative and descriptive trajectories. Through the combination of different modes of the landscape’s description, through its successive spatialization across different agendas of movement and occupation, ‘Foray in a Modern Reserve’ constructs a utopic portrait of the modern reservoir reserve. As a composite text, it traces the intersection and dispersal of desire and agency across the terrain as an ‘inspection’ that must discover and construct its own object, and propose its own figural ‘solution’ to the landscape’s latent equations.